Phenotype, Polyfunctionality, and Antiviral Activity of in vitro Stimulated CD8+ T-Cells From HIV+ Subjects Who Initiated cART at Different Time-Points After Acute Infection - Salido, Jimena; Ruiz, María Julia; Trifone, César; Figueroa, María Inés; Caruso, María Paula; Gherardi, María Magdalena; Sued, Omar; Salomón, Horacio; Laufer, Natalia; Ghiglione, Yanina; Turk, Gabriela (Frontiers in Immunology, 2018)
Since anti-HIV treatment cannot cure the infection, many strategies have been proposed to eradicate the viral reservoir, which still remains as a major challenge. The success of some of these strategies will rely on the ability of HIV-specific CD8+ T-cells (CD8TC) to clear reactivated infected cells. Here, we aimed to investigate the phenotype and function of in vitro expanded CD8TC obtained from HIV+ subjects on combination antiretroviral therapy (cART), either initiated earlier (median=3 months postinfection, ET: Early treatment) or later (median=20 months postinfection, DT: Delayed treatment) after infection. Peripheral blood mononuclear cells from 12 DT and 13 ET subjects were obtained and stimulated with Nef and Gag peptide pools plus IL-2 for 14 days. ELISPOT was performed pre- and post-expansion. CD8TC memory/effector phenotype, PD-1 expression, polyfunctionality (CD107a/b, IFN-, IL-2, CCL4 (MIP-1β) and/or TNF-α production) and antiviral activity were evaluated post-expansion. Magnitude of ELISPOT responses increased after expansion by 103 times, in both groups. Expanded cells were highly polyfunctional, regardless of time of cART initiation. The memory/effector phenotype distribution was sharply skewed towards an effector phenotype after expansion in both groups although ET subjects showed significantly higher proportions of stem-cell and central memory CD8TCs. PD-1 expression was clustered in HIV-specific effector memory CD8TCs, subset that also showed the highest proportion of cytokine–producing cells. Moreover, PD-1 expression directly correlated with CD8TC functionality. Expanded CD8TCs from DT and ET subjects were highly capable of mediating antiviral activity, measured by two different assays. Antiviral function directly correlated with the proportion of fully differentiated effector cells (viral inhibition assay) as well as with CD8TC polyfunctionality and PD-1 expression (VITAL assay). In sum, we show that, despite being dampened in subjects on cART, the HIV-specific CD8TC response could be selectively stimulated and expanded in vitro, presenting a high proportion of cells able to carry-out multiple effector functions. Timing of cART initiation had an impact on the memory/effector differentiation phenotype, most likely reflecting how different periods of antigen persistence affected immune function. Overall, these results have important implications for the design and evaluation of strategies aimed at modulating CD8TCs to achieve the HIV functional cure.